2022
DOI: 10.3390/molecules27103088
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Catalytic Alkyne Transformation via Copper Carbene Intermediates

Abstract: As one of the abundant and inexpensive metals on the earth, copper has demonstrated broad applications in synthetic chemistry and catalysis. Among these copper-catalyzed advances, copper carbenes are versatile and reactive intermediates that can mediate a variety of transformations, which have attracted much attention in the past decades. The present review summarizes two different reaction models that take place between a copper carbene intermediate and alkyne species, including the cross-coupling reaction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 173 publications
(172 reference statements)
0
5
0
Order By: Relevance
“…The domino functionalization of alkynes mainly involves simultaneous C-C and C-X bond-forming events. [11][12][13][14][15][16][17][18] In this context, the vicinal/geminal cascade functionalization of alkynes involving the C-C and C-O bond formation reaction has been thoroughly studied and numerous elegant approaches have been described in the literature. Different modes of cascades are described in Fig.…”
Section: Subhra Sriharsa Beheramentioning
confidence: 99%
“…The domino functionalization of alkynes mainly involves simultaneous C-C and C-X bond-forming events. [11][12][13][14][15][16][17][18] In this context, the vicinal/geminal cascade functionalization of alkynes involving the C-C and C-O bond formation reaction has been thoroughly studied and numerous elegant approaches have been described in the literature. Different modes of cascades are described in Fig.…”
Section: Subhra Sriharsa Beheramentioning
confidence: 99%
“…Several reviews discuss the role of the metal salts and organic ligands [73][74][75][76][77][78][79] and address catalyst design parameters. These include operational stability and a partially saturated coordination environment fulfilled by ligands bearing two or three heteroatoms.…”
Section: Trial Experiments Includementioning
confidence: 99%
“…16 The A 3 coupling reaction is a popular organic pathway for synthesizing PAs in the presence of late (Cu, Pd, or Au) transition metals. [17][18][19][20][21][22][23][24][25][26][27][28][29] This process involves three substrates, amine-alkyne-aldehyde and the in situ formation of a p complex (metal-alkyne), which weakens the C-H sp bond with subsequent proton elimination by a weak base, resulting in s activation and formation of the acetylide, which can be subsequently added to the imine (product of the amine-aldehyde condensation), yielding the PA. 14 The A 3 coupling reaction has been a desirable target for mechanochemical synthesis, as it allows for the rapid and efficient construction of complex molecules with high structural diversity. In 2015, Su et al demonstrated a solvent-free enantioselective PAs synthesis via a Cu(OTf) 2 /Phpybox system by ball-milling within 60 minutes.…”
Section: Introductionmentioning
confidence: 99%